2021
DOI: 10.1186/s13048-021-00904-y
|View full text |Cite
|
Sign up to set email alerts
|

Cocultured porcine granulosa cells respond to excess non-esterified fatty acids during in vitro maturation

Abstract: Background Non-esterified fatty acids (NEFAs) are one of the main lipid components of follicular fluid at concentrations that depend on circulating levels. Elevated levels of NEFAs impair oocyte quality, development potential, and may subsequently influence the metabolism and reproductive fitness of offspring. Granulosa cells (GCs) are the follicular cells that are closely communicating with the oocyte. However, the responses of GCs exposed to high levels of NEFAs when cocultured with cumulus-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Supplementation of NEFA also had negative effects on porcine granulosa cell proliferation and viability and increased the lipid content in granulosa and cumulus cells ( Ogawa et al 2018 , Pawlak et al 2020 , Shibahara et al 2020 ). Besides, the high level of NEFA altered transcriptomic pattern which is enriched in pathways related to metabolism, inflammation, and impaired mitochondrial function in granulosa cells ( Shi & Sirard 2021 a ). After ovulation, the epithelial–mesenchymal transition (EMT) of granulosa cells to luteal cells occurs, which is associated with changes in estradiol and progesterone production.…”
Section: Oocyte Maturation and Its Subsequent Development Are Sensiti...mentioning
confidence: 99%
See 3 more Smart Citations
“…Supplementation of NEFA also had negative effects on porcine granulosa cell proliferation and viability and increased the lipid content in granulosa and cumulus cells ( Ogawa et al 2018 , Pawlak et al 2020 , Shibahara et al 2020 ). Besides, the high level of NEFA altered transcriptomic pattern which is enriched in pathways related to metabolism, inflammation, and impaired mitochondrial function in granulosa cells ( Shi & Sirard 2021 a ). After ovulation, the epithelial–mesenchymal transition (EMT) of granulosa cells to luteal cells occurs, which is associated with changes in estradiol and progesterone production.…”
Section: Oocyte Maturation and Its Subsequent Development Are Sensiti...mentioning
confidence: 99%
“…After ovulation, the epithelial–mesenchymal transition (EMT) of granulosa cells to luteal cells occurs, which is associated with changes in estradiol and progesterone production. Inhibition of EMT and altered steroidogenesis in response to high levels of NEFA partly explain the anovulation and impaired follicle development observed in pathological nutritional status ( Foong et al 2006 , Chaput & Sirard 2020 , Shi & Sirard 2021 a ). Moreover, supplementation with NEFA during IVM also decreased the blastocyst formation ( Shibahara et al 2020 , Shi & Sirard 2021 c ).…”
Section: Oocyte Maturation and Its Subsequent Development Are Sensiti...mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous articles are conducted to explore GCs-related gene functions as well as the precise mechanisms. Previous studies have suggested that miRNAs ( Tian et al, 2020 ; Toms et al, 2021 ), lncRNAs ( Hu et al, 2021 ; Meng et al, 2021 ; Ruszkowska et al, 2018 ; Zhang et al, 2019 ) and mRNAs ( Kulus et al, 2021 ; LaVoie, 2017 ; Shi & Sirard, 2021 ) have critical effects on modulating GCs function along with follicular development in pigs. In addition, for precursor-messenger RNAs (pre-mRNAs), their post-transcriptional modifications like alternative polyadenylation (APA) and alternative splicing (AS) enrich the proteome diversity and have critical effect in different tissues and different developmental stages ( Baralle & Giudice, 2017 ; Di Giammartino, Nishida & Manley, 2011 ; Gruber & Zavolan, 2019 ).…”
Section: Introductionmentioning
confidence: 99%